The Effectiveness of the Waste Management Program Through Waste Banks in Regol District, Bandung City - Rizky Muhyidin Mukti; Rina Mutiarawati; Ibnu Malik (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Urban waste growth and limited local processing capacity have intensified the need to evaluate waste bank programmes in Bandung City. This study evaluates the effectiveness of the Waste Bank Programme in Regol District using Sutrisno’s five dimensions: programme understanding, target accuracy, timeliness, goal attainment, and tangible change. A qualitative descriptive design was employed, with data collected through semi-structured interviews, direct observation, and document analysis from purposively selected government officials, programme managers, participants, and environmental actors. The findings show that the programme was moderately effective. Customer participation increased from approximately 30 to 97 people, 421 kilograms of inorganic waste were recovered, customer savings reached about IDR 4.4 million, and financial turnover totalled IDR 15 million. The programme improved household waste sorting and awareness of waste’s economic value, but limited storage capacity, weak business-sector participation, and incomplete neighbourhood coverage constrained environmental impacts. Strengthening infrastructure, institutional coordination, and programme expansion is therefore essential.